Medidas socioeducativas de privação de liberdade no Brasil: uma revisão sistemática de literatura - Gontijo, Daniella Ribeiro (2019)
The objective of this research was to map the articles published since 1990 on the educational correctional measure of deprivation of liberty applied to adolescents in Brazil. We adopted a systematic review of the literature and based on the guiding question "What are the contributions of correctional measure of deprivation of liberty for the development of young people in Brazil?", a search was made in the literature based on the following criteria: (a) complete published articles since 1990 - the period of the ECA promulgation; (b) in the electronic bases Scielo, Lilacs, Pepsic and Adolec; (c) from the keywords, suggested by the descriptors in Science and Health (DECS) available on the VHL site, used in a combined way: adolescents, institutionalized, health of the institutionalized adolescents, minor, Home Foundation, juvenile delinquency, conflict with the law, correctional measure, youth, adolescents and adolescence; (d) published in Portuguese. Initially 4088 titles were found and after applying the exclusion criteria, the corpus of analysis consisted of 56 articles. It was verified that the articles were published mainly in Psychology journals, being the first authors linked to institutions of the Southeast region, which concentrates most of the post-graduation in Brazil. The thematic analysis of the results of the selected articles pointed to the following axes: (1) Structure of the units of correctional measure of deprivation of liberty; (2) Operation of deprivation of liberty MSE units; (3) Practices developed for young people who fulfilled correctional measure of deprivation of liberty; (4) Adolescent mental health: dangerousness and psychiatry; (5) Absent or almost: Do families and adolescents also speak? The results indicated that characteristics that go back to the old model of the Code of Minors and characteristics of the prison model prevail in practices with adolescents, which is expressed through punishment, violations of rights and violence. The distance between what is advocated in the law and what actually occurs in relation to the various aspects: structural, functioning and practices is perceived. The application of the measure of deprivation of liberty in the analyzed articles does not indicate that the objective of reintegration has been reached. On the contrary, deprivation of liberty imposed on adolescents who have committed acts of infraction seems to favor the removal of those who "represent danger" from the field of view of society.